ETHICAL DIMENSIONS OF WILLINGNESS TO PAY FOR MEDICAL CARE IN BULGARIA - Peycheva, Kalina; Deliverska, Mariela (International Journal of Research -GRANTHAALAYAH, 2018)
Regardless of what both patients and medical professionals might think, nowadays there is no free medicine. The need of changing the pattern is emphasized and people should become more responsible for their own health. The aim is to find a connection between the trust in GPs, prophylactic check-ups, new methods of treatment and the willingness of patients to pay for the received medical services. Material and Method: A questionnaire was prepared for the purposes of the study. The methods utilized were a direct individual anonymous questionnaire, statistical – descriptive, analytical (Chi-square). The answers were examined and statistically processed according to age, gender and education level of the participants. Results: 1. The results regarding the trust in GP is very unconvincing – only 14,5 % believe in their GP. 2. The percentage of believers in prophylactic check-ups is high - 57,9%. 3.The percentage of those who believe in the new methods and means for treatment is high, over 80%, while no difference is found with respect to the patients’ education level. 4. The patients often (86%) pay for the treatment of a specialist. 5. People with higher education more readily pay for medical care. Conclusions: 1. The lack of trust in GP combined with the strong belief in prophylactic check - ups and the new methods for diagnostic and treatment of diseases lead to higher expectations of patients towards the medical services and their readiness to pay for these services. 2. The patients indicate readiness to pay for medical services which is a part of the patients’ readiness to take care for their own health.